Characteristics of the menstrual cycle and hormonal contraceptive use in elite Spanish basketball players - Crespo, Pilar; Herranz, Nuria; Estella, Víctor; Morencos, Esther; Herranz, María; Rodas, Gil (Frontiers in Sports and Active Living, 2025)
IntroductionPrevious research has shown how menstrual-related symptoms (e.g., abdominal cramps, tiredness/fatigue) can limit athletes’ ability to train. Nonetheless, the specific characteristics of the menstrual cycle (MC) and their relationship with performance, well-being, and injuries in athletes are not well understood. This cross-sectional study aimed to better understand the characteristics of the MC (menarche, length, dysmenorrhea, amenorrhea, etc.) and the use of hormonal contraceptives among the elite Spanish basketball players.MethodsA total of 228 healthy elite female basketball players from both first division and second division of the Spanish league were included in this cross-sectional study. Subjects were assessed for MC characteristics using a validated questionnaire.ResultsThe menarche age in the study population was 13.21 ± 1.55 years. The majority of players (78.51%) experienced a regular MC of 27.69 ± 3.78 days, with a range from 17 to 40 days. One hundred ninety-eight out of the 228 players surveyed (86.84%) experienced dysmenorrhea during their periods, and 41.67% took pain medication. Moreover, 77.63% of the players showed symptoms of premenstrual syndrome. Amenorrhea was also reported by 22.81% of them, and 3.51% of the players had been pregnant at some point in their lives. No statistically significant differences were observed when comparing the characteristics of the MC between first and second division players. Less than a quarter of the studied population referred using hormonal contraceptives regularly.ConclusionMC alterations are prevalent among female basketball players. More research is necessary to understand how this can affect the quality of life, the performance, and the injury susceptibility of female athletes.